De Novo Germline Mutations in SEMA5A Associated With Infantile Spasms - Wang, Qiongdan; Liu, Zhenwei; Lin, Zhongdong; Zhang, Ru; Lu, Yutian; Su, Weijue; Li, Feng; Xu, Xi; Tu, Mengyun; Lou, Yongliang; Zhao, Junzhao; Zheng, Xiaoqun (Frontiers in Genetics, 2019)
Infantile spasms (IS) is an early-onset epileptic encephalopathy that is usually presented with hypsarrhythmia on electroencephalogram and developmental retardation or regression. In this study, whole-exome sequencing was performed to detect potential pathogenic de novo mutations, and finally we identified a novel damaging de novo mutation in SEMA5A and a compound heterozygous mutation in CLTCL1 in three sporadic trios with IS. The expression profiling of SEMA5A in human brain showed that it was mainly highly expressed in the cerebral cortex during early brain development stage (8-9 post-conception weeks and 0-5 month after birth). In addition, we identified a close protein-protein interaction network between SEMA5A and candidate genes associated with epilepsy, autism spectrum disorder (ASD) or intellectual disability. Gene enrichment and function analysis demonstrated that genes interacting with SEMA5A were significantly enriched in several brain regions across early fetal development, including the cortex, cerebellum, striatum and thalamus (q<0.05), and were involved in axonal, neuronal and synapse-associated processes. Furthermore, SEMA5A and its interacting genes were associated with ASD, epilepsy syndrome and developmental disorders of mental health. Our results provide insightful information indicating that SEMA5A may contribute to the development of the brain and be associated with IS. However, further genetic studies are still needed to evaluate the role of SEMA5A in IS and definitively establish the role of SEMA5A in this disorder.